Lifting Confidentiality of FRAND Royalties in SEP Arbitration - Kim, Yoonhee (Science and Technology Law Review, 2014)
No patent dispute in recent years draws more attention than the “Smartphone Wars.” At the center stage of the Smartphone Wars is the “fair, reasonable, and non-discriminatory (FRAND)” commitment to license standard-essential patents (SEPs). Later added to the stage is the new form of SEP enforcement targeting small businesses and end-users. As a result, the efficacy of FRAND commitments comes under criticism from the antitrust enforcement agency, leading scholars, and the President of the United States. With a view to breathing life into the meaning of “FRAND,” this Article explores arguments against confidentiality of FRAND royalties in SEP arbitration, primarily focusing on an analogy to section 294 of the Patent Act. Section 294 may provide an adequate platform for this discussion because it already lifted confidentiality of patent validity and infringement in the interest of the public and competition. Similarly, lifting confidentiality of FRAND royalties in SEP arbitration could be an effective measure to tackle unfair competition and deceptive business practices and to empower the public in the Smartphone Wars and in the face of SEP enforcement.